2010
DOI: 10.1159/000276593
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of Intestinal Epithelial Cells Mediated by Cell Confluence and/or Exogenous Nucleoside Supplementation

Abstract: Nucleotides (NT) and nucleosides (NS) play a key role in gastrointestinal development and in enterocyte healing after tissue damage. Exogenous NT and NS may therefore represent a novel therapy for maintaining gastrointestinal tract integrity. An exogenous NS mixture of thymidine, cytidine, guanosine and inosine (T-CGI) increases the proliferation rate of rat intestinal epithelial cell line 6 (IEC-6) cells, while a mixture of uridine, cytidine, guanosine and inosine (U-CGI) reduces IEC-6 proliferation independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 100 publications
(64 reference statements)
3
11
0
Order By: Relevance
“…However, villin is expressed when IEC-6 cells are grown beyond confluence [28] and butyric acid stimulates differentiation in those cells [17]. Our previous results also support a direct role for Slfn3 in IEC-6 differentiation in response to several exogenous stimuli [12].…”
Section: Discussionsupporting
confidence: 70%
“…However, villin is expressed when IEC-6 cells are grown beyond confluence [28] and butyric acid stimulates differentiation in those cells [17]. Our previous results also support a direct role for Slfn3 in IEC-6 differentiation in response to several exogenous stimuli [12].…”
Section: Discussionsupporting
confidence: 70%
“…The immune parameters often found increased following feeding these diets include respiratory burst activity, plasma complement activity, serum lysozyme activity, and proliferative responses of lymphocytes to mitogens [39,60,74]. Often the immunostimulants can provide improved protection against a number of pathogenic bacteria including Aeromonas spp [75], Vibrio spp.…”
Section: Immunostimulantsmentioning
confidence: 99%
“…Both the de novo synthesis and salvage pathways are energy consuming and hence a ready supply of dietary nucleotides may be beneficial to rapidly proliferating tissue, such as the gastrointestinal tract [74]. Much of the nucleotide synthesis and salvage is performed in the liver and many cell types such as immune cells have a limited ability to synthesise nucleotides and rely on the supply of preformed molecules.…”
Section: Nucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…guanosine ? inosine) (Rodríguez-Serrano et al 2010), TNF-a, IFN-c (Kolinska et al 2008), gastrin (Wang et al 2003), and Matrigel (Carroll et al 1988) have been reported to effectively induce IEC-6 cell differentiation.…”
Section: Introductionmentioning
confidence: 99%